Anti-Toxoplasma gondii antibodies in patients with schizophrenia-preliminary findings in a Turkish sample - Cetinkaya, Zafer; Yazar, Suleyman; Gecici, Omer; Namli, Mustafa N. (Oxford Univ Press, 2007)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. We investigated the seropositivity rate for anti-Toxoplasma IgG and IgNI antibodies by enzymelinked immunosorbent assay (ELISA) in patients with schizophrenia to ascertain a possible relationship between Toxoplasma gondii and schizophrenia. We selected 100 patients with schizophrenia, 50 with depressive disorder, and 50 healthy volunteers to investigate the seropositivity rate of anti-Toxoplasma antibodies by ELISA. The seropositivity rate for anti-Toxoplasma IgG antibodies among schizophrenia patients (66%) was significantly higher than among patients with depressive disorder or healthy volunteers (P <.01). Thus, there might be a causal relationship between toxoplasmosis and the etiology of schizophrenia.
Keywords: schizophrenia; Toxoplasma gondii; ELISA